Effectiveness of seasonal influenza vaccine for adults and children in preventing laboratory-confirmed influenza in primary care in the United Kingdom: 2015/16 end-of-season results - Pebody, R; Warburton, F; Ellis, J; Andrews, N; Potts, A; Cottrell, S; Johnston, J; Reynolds, A; Gunson, R; Thompson, C; Galiano, M; Robertson, C; et al. (European Centre for Disease Prevention and Control, 2016)
The United Kingdom (UK) is in the third season of introducing universal paediatric influenza vaccination with a quadrivalent live attenuated influenza vaccine (LAIV). The 2015/16 season in the UK was initially dominated by influenza A(H1N1)pdm09 and then influenza of B/Victoria lineage, not contained in that season's adult trivalent inactivated influenza vaccine (IIV). Overall adjusted end-of-season vaccine effectiveness (VE) was 52.4% (95% confidence interval (CI): 41.0-61.6) against influenza-confirmed primary care consultation, 54.5% (95% CI: 41.6-64.5) against influenza A(H1N1)pdm09 and 54.2% (95% CI: 33.1-68.6) against influenza B. In 2-17 year-olds, adjusted VE for LAIV was 57.6% (95% CI: 25.1 to 76.0) against any influenza, 81.4% (95% CI: 39.6-94.3) against influenza B and 41.5% (95% CI: -8.5 to 68.5) against influenza A(H1N1)pdm09. These estimates demonstrate moderate to good levels of protection, particularly against influenza B in children, but relatively less against influenza A(H1N1)pdm09. Despite lineage mismatch in the trivalent IIV, adults younger than 65 years were still protected against influenza B. These results provide reassurance for the UK to continue its influenza immunisation programme planned for 2016/17.